2009
DOI: 10.1145/1477926.1477928
|View full text |Cite
|
Sign up to set email alerts
|

A variational approach for automatic generation of panoramic maps

Abstract: Panoramic maps combine the advantages of both ordinary geographic maps and terrestrial images. While inheriting the familiar perspective of terrestrial images, they provide a good overview and avoid occlusion of important geographical features. The designer achieves this by skillful choice and integration of several views in a single image. As important features on the surface must be carefully rearranged to guarantee their visibility, the manual design of panoramic maps requires many hours of tedious and pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…However, the large distortions of the resulting zigzagging and twisted routes often caused misleading navigation for users. Later Degener and Klein [14] presented a variational approach to generate panoramic maps in mountain areas. This approach can provide a good overview and it avoids the occlusion of important geographical features; however, it also requires considerable computation.…”
Section: Visualization Of Foimentioning
confidence: 99%
“…However, the large distortions of the resulting zigzagging and twisted routes often caused misleading navigation for users. Later Degener and Klein [14] presented a variational approach to generate panoramic maps in mountain areas. This approach can provide a good overview and it avoids the occlusion of important geographical features; however, it also requires considerable computation.…”
Section: Visualization Of Foimentioning
confidence: 99%
“…Alternatively, elevation information can be represented by applying projections that deviate from the traditional, orthographic top-down views-such as perspective, cylindrical, or oblique projections [12]. Mapmakers may also create views that distort the underlying map to emphasize specific terrain features [6,13]. The panorama maps often used to show ski slopes are a common example of this technique.…”
Section: Relief Rendering Techniquesmentioning
confidence: 99%
“…This work has been followed by an approach by Möser et al [15], where they distorted the terrain surface to be aligned with the predefined base surface to reduce possible occlusions of geographic features. Degener and Klein [6] constructed a variational formulation for automating occlusion-free representation of ski and hiking courses in mountain areas. Cui et al [5] implemented GPUaccelerated techniques for occlusion-free visualization and demonstrated real-time navigation in canyon terrain areas.…”
Section: Related Workmentioning
confidence: 99%